2007
DOI: 10.1074/jbc.m606477200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reduced Lipoic Acid in the Redox Regulation of Mitochondrial Aldehyde Dehydrogenase (ALDH-2) Activity

Abstract: Chronic therapy with nitroglycerin results in a rapid development of nitrate tolerance, which is associated with an increased production of reactive oxygen species. We have recently shown that mitochondria are an important source of nitroglycerin-induced oxidants and that the nitroglycerin-bioactivating mitochondrial aldehyde dehydrogenase is oxidatively inactivated in the setting of tolerance. Here we investigated the effect of various oxidants on aldehyde dehydrogenase activity and its restoration by dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
117
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 40 publications
7
117
0
Order By: Relevance
“…Others have shown that over-expression of ALDH2 can downregulate ROS generation and protect against oxidative stress Choi et al 2011). Studies have also demonstrated that α-LA could increase ALDH2 activity by ~ 60% in isolated rat heart mitochondria (Wenzel et al 2007). Our results from the present study showed that α-LA was able to significantly reduce serum levels of 8-iso-PGF2α, which was accompanied by up-regulation of ALDH2 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that over-expression of ALDH2 can downregulate ROS generation and protect against oxidative stress Choi et al 2011). Studies have also demonstrated that α-LA could increase ALDH2 activity by ~ 60% in isolated rat heart mitochondria (Wenzel et al 2007). Our results from the present study showed that α-LA was able to significantly reduce serum levels of 8-iso-PGF2α, which was accompanied by up-regulation of ALDH2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, α-LA was reported to increase the activity of mitochondrial aldehyde dehydrogenase-2 (ALDH2) by ~ 60% in isolated rat heart mitochondria (Wenzel et al 2007). ALDH2, the main enzyme responsible for acetaldehyde oxidation in ethanol metabolism, is thought to be responsible for oxidation and detoxification of aromatic and aliphatic aldehydes (Bosron and Li 1986;Ohsawa et al 2003;Vasiliou and Nebert 2005;Bian et al 2010).…”
mentioning
confidence: 99%
“…Oxidative stress may be a decisive component in the development of nitrate tolerance (Munzel et al, 1999;Jurt et al, 2001;Csont and Ferdinandy, 2005;Wenzel et al, 2007). Recent studies have indicated that ALDH-2 is the main enzyme responsible for nitroglycerin bioactivation, and that inhibition of this enzyme contributes to nitrate tolerance (Chen et al, 2002;Sydow et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that ALDH-2 is the main enzyme responsible for nitroglycerin bioactivation, and that inhibition of this enzyme contributes to nitrate tolerance (Chen et al, 2002;Sydow et al, 2004). There is evidence that oxidants can inactivate ALDH-2 directly and induce nitrate tolerance Wenzel et al, 2007). Oxidative stress may contribute directly to nitroglycerin tolerance, either by oxidative inhibition of ALDH-2 or perhaps by oxidizing key enzyme cofactors (Chen et al, 2002;Sydow et al, 2004;Daiber et al, 2004;Munzel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation